Methodist Missionary Society archives, London, [on microfiche] ([IDC microedition] ;, 1982)
Methodist synod minutes for Rhodesia,1892-1922, Southern Rhodesia, 1934-1939, Northern Rhodesia, 1932-1944, and Transvaal and Swaziland, 1889-1943.